Urgency to treat patients with chronic hepatitis C in Asia. Issue 5 (27th April 2017) - Kao, Jia‐Horng; Ahn, Sang Hoon; Chien, Rong‐Nan; Cho, Mong; Chuang, Wan‐Long; Jeong, Sook‐Hyang; Liu, Chen‐Hua; Paik, Seung‐Woon
Abstract: Chronic hepatitis C (CHC) infection poses a global healthcare burden, being associated with serious complications if untreated. The prevalence of hepatitis C virus (HCV) infection is highest in areas of Central, South, and East Asia; over 50% of HCV patients worldwide live in the region, where HCV genotypes 1b, 2, 3, and 6 are the most prevalent. Treatment outcomes for chronic hepatitis C vary by ethnicity, and Asian patients achieve higher sustained virologic response rates following interferon (IFN)‐based therapy than non‐Asians. However, low efficacy, poor safety profile, and subcutaneous administration limit the use of IFN‐based therapies. Superior virologic outcomes have been observed with different classes of direct‐acting antivirals (DAAs) alone or in combination, and several all‐oral DAA regimens are available in Asia. These regimens have shown excellent efficacy and favorable tolerability in clinical trials, yet there is a need for further studies of DAAs in a real world context, particularly in Asia. Furthermore, IFN‐free treatment may not be accessible for many patients in the region, and IFN‐based regimens remain an option in some countries. There is a need to improve current clinical practices for HCV management in Asia, including effective screening, disease awareness, and prevention programs, and to further understand the cost‐effectiveness of IFN‐free regimens. The evolution of potent treatments makes HCV eradication a possibility that should be available to all patients. However, access to these therapies in Asian countries has been slow, primarily because of economic barriers that continue to present a hurdle to optimal treatment.